Pengaruh Variasi Nilai Hydrophylic-lipophylic balance dan Suhu terhadap Karakteristik Sediaan Krim - Suardana, I Made; Suhendra, Lutfi; Wrasiati, Luh Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 8 No 2 (2020): Juni, 2020)
This study aims to determine the effect of hydrophylic-lipophylic balance value and process temperature on the characteristics of the best cream preparations and to determine the hydrophylic-Lipophylic balance value and the best process temperature for obtaining cream preparations. This research uses factorial randomized block design. The first factor is hydrophylic-lipophylic balance which consists of 4 levels, namely: A1; 12, A2; 11, A3; 10, A4; 9. The second factor is the process temperature consisting of 3 levels, namely: B1; 60±2°C, B2; 70±2°C, B3; 80±2°C. Each treatment was grouped into 2 based on the time of implementation so that 24 experimental units were obtained. the observed variables were homogeneity, separation ratio, dispersion, adhesion, pH and viscosity. The data obtained were then analyzed by analysis of variance and continued using the Tukey test. To determine the best treatment of all parameters, the effectiveness index test was measured. The results showed that the treatment of  h ydrophylic- l ipophylic  b alance and temperature greatly influenced the value of the separation ratio, viscosity, adhesion and dispersion, but did not affect the homogeneity and pH of the cream preparation. Hydrophylic-lipophylic balance 10 treatment with a temperature of 70±2°C is the best treatment to produce cream preparations, with homogeneous characteristics, a separation ratio of 1,000 ± 0,000, spreadability of 5.500 ± 0.070 cm, adhesion of 16.610 ± 0.665 seconds, viscosity of 34,000 ± 2,830 cPs , and pH 5,600 ± 0,000. Keywords:  Temperature,  H ydrophylic-lipophylic balance, Surfactant, Tween 80 and Span 80.